Modification of Bonding Strength Test of WC HVOF Thermal Spray Coating on Rocket Nozzle - Sofyan, Bondan T.; Pardede, Haposan J.; Stefano, Marizki; Sofyan, Edi (Makara Journal of Technology, 2006)
Modification of Bonding Strength Test of WC HVOF Thermal Spray Coating on Rocket Nozzle. One way to reduce structural weight of RX-100 rocket is by modifying the nozzle material and processing. Nozzle is the main target in weight reduction due to the fact that it contributes 30 % to the total weight of the structur. An alternative for this is by substitution of massive graphite, which is currently used as thermal protector in the nozzle, with thin layer of HVOF (High Velocity Oxy-Fuel) thermal spray layer. This paper presents the characterization of nozzle base material as well as the modification of bonding strength test, by designing additional jig to facilitate testing processes while maintaining level of test accuracy. The results showed that the material used for RX-100 rocket nozzle is confirmed to be S45C steel. Modification of the bonding strength test was conducted by utilizing chains, which improve test flexibility and maintains level of accuracy of the test.